THE PUBLIC AND THE PRIVATE IN THE PUBLIC SPACE MALECÓN SIMÓN BOLÍVAR: RELATIONS OF POWER AND CITIZENSHIP - Marcela Blacio-Valdivieso (Daya, 2018)
Gentrification is a concept that has been applied essentially to urban areas except on its analysis of public spaces. Our approach is focused on a special way of analyzing gentrification in non-residential areas. One of these areas is the public space known as Malecón Simón Bolívar in the city of Guayaquil. We want to demonstrate that the gentrification that has operated in this emblematic project of Guayaquil urban regeneration is essentially commercial and cultural. To do this we did a documentary research -on the history of Guayaquil, its port and its boardwalk, delving into social, economic, cultural and political aspects- and a field research- survey, interviews, and photoetnography- focused on testing the mechanisms that, in form of devices and imaginaries, they process a sui generis gentrification in the public space. The results of this research show a private appropriation, processed over 20 years, in the form of an offer for commercial and cultural consumption in the space that should belong to everyone. Likewise, of some devices: financial, urban, civic and social and some social imaginaries that deepen the privatization of public space.